Root architecture modification in response to phosphorus and nitrogen availability - Silva, Adriano Alves da; Delatorre, Carla Andréa (Revista de Ciências Agroveterinárias, 2009)
Nutrient availability is a common soil restriction for plant growth and development. Plants have evolved mechanisms to cope with this kind of stress, such as root architecture remodeling. Changes in root architecture may cause differential soil exploration ability, affecting nutrient uptake. Root architecture might be affected not only by nutrient availability but also by its soil mobility. Phosphorus limitation, a non-mobile nutrient, produces a shallow and branched root system, increasing the volume of exploited soil. Nitrogen limitation, a high-mobile nutrient, does not affect primary root growth. However, high nitrogen patches increase local lateral root initiation and elongation. The knowledge about sensors and transduction pathways is still scarce. There are emerging evidences for crosstalk between nutrient signaling pathways. Understanding the acclimation responses to nutrient availability, considering the interactive and hierarchical regulation of signaling pathways, is essential for adequate growth modeling and output prediction. Increased in the efficiency of nutrient uptake and use may reduce costs and promote better resources allocation, improving agriculture sustainability.